2022
DOI: 10.1002/ajoc.202200330
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous First‐row Transition‐metal‐catalyzed Carbon Dioxide Hydrogenation to Formic Acid/Formate, and Methanol

Abstract: Depletion of fossil fuel for global energy need emits large amount of greenhouse gas carbon dioxide into the biosphere. Carbon dioxide constitutes a sustainable C1 feedstock and cost‐effective raw material for the synthesis of bulk and fine chemicals. The catalytic hydrogenation of CO2 to formic acid, and methanol is an attractive protocol owing to their application in chemical industry and as potential renewable hydrogen storage materials. Catalytic hydrogenation reactions are atom‐economical, green and susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 174 publications
0
18
0
Order By: Relevance
“…Furthermore, a relatively sharp resonance corresponding to the hydroxyl group was also present at 11.80 ppm. The corresponding 13 C{ 1 H} NMR spectrum for [2] OTf also suggested that the phosphorus ligand was in the 6-D i PPin form in the [2] + complexes. The signal corresponding to the quaternary carbon containing a hydroxyl group was located at 166.4 ppm as a doublet (J PC = 16.5 Hz).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, a relatively sharp resonance corresponding to the hydroxyl group was also present at 11.80 ppm. The corresponding 13 C{ 1 H} NMR spectrum for [2] OTf also suggested that the phosphorus ligand was in the 6-D i PPin form in the [2] + complexes. The signal corresponding to the quaternary carbon containing a hydroxyl group was located at 166.4 ppm as a doublet (J PC = 16.5 Hz).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The interconversions between the 6-D i PPin and 6-D i PPon* ligand forms offer potential for the activation of small molecules via metal–ligand cooperative mechanisms. It was therefore of interest to explore the catalytic reactivity of these complexes for the hydrogenation of CO 2 . In accordance with typically utilized reaction conditions, the application of complex 1 or [ 2 ] OTf for the catalytic hydrogenation of CO 2 in the presence of a base was investigated. DBU was chosen as the base to provide [DBU + H]­[OC­(O)­H] as the reaction product (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A fascinating TON number was obtained during the hydrogenation of CO 2 to formic acid with various homogeneous catalysts. [7][8][9][10] Despite such exceptional performance, the troublesome separation and recycling of metal complexes, as well as the use of costly and air-sensitive ligands, offer significant barriers in the practical deployment of such molecular complexes. 11 However, the ease of separation, handling, and recyclability of heterogeneous catalysts, which are especially favorable for continuous operation in practice, has inspired substantial research efforts to realize the heterogeneous catalytic synthesis of formic acid through CO 2 hydrogenation.…”
Section: Introductionmentioning
confidence: 99%